Knowledge, Attitude, and Practices in Prevention of Respiratory Infectious Diseases among Patients Receiving Services at an Outpatient Department: Saharat Ngammuangpak - ngammuangpak, sahrath; Unahalekhaka, Akeau; Lertwatthanawilat, Wanchai (Princess of Naradhiwas University Journal, 2024)
Respiratory infectious diseases have severe and long-lasting impacts on the population. This descriptive study aims to determine the knowledge, attitude, and practices in prevention of respiratory infectious diseases among patients receiving services at an outpatient department, and to examine the relationship between knowledge, attitude, and practices in prevention of respiratory infectious diseases. Samples included 400 patients who had received services at the outpatient department of a university hospital in the Northern region during July to October 2022. The study instrument was a self-administered questionnaire related to knowledge, attitude, and practices in prevention of respiratory infectious diseases consisting of general information, knowledge, attitude, and practices in prevention of respiratory infectious diseases. Data were analyzed using descriptive statistics, and Spearman’s correlation coefficient was used to analyze the relationship among knowledge, attitude, and practices in prevention of respiratory infectious diseases. The study results showed that the knowledge, attitude, and practices in prevention of respiratory infectious diseases of the participants were at a high level. Knowledge had a very low level of positive correlation with attitude in prevention of respiratory infectious diseases (r = .239, p < 0.01). Attitude had a low level of positive correlation with practices in prevention of respiratory infectious diseases (r = .306, p < 0.01), and knowledge had a very low level of positive correlation with practices in prevention of respiratory infectious diseases (r = .300, p < 0.01). The study results provide guidelines for educating and promoting practices in prevention of respiratory infectious diseases for patients receiving services at outpatient department.